House of Representative Dubious Authority Study of Selection Committee Existence for the Central Indonesian Broadcasting Commission Member - Mamulai, Muslim; Ahmad, Ahmad (Universitas Muhammadiyah Ponorogo, 2019)
Selection for commission member of Central Indonesian Broadcasting is administered by house of representative; nonetheless, the implementation is managed by the selection committee formed by the ministry of Communication and Information. The house of representative will conduct proper test to selection committee in order to examine the element of community and academic capacity within broadcasting field. Indonesian Ministry of Communication and information as the official has unjustly determined lists of Central Indonesian Broadcasting Commission Member candidates that has passed proper test selection by the house of representative. As a result, it harms those who do not qualify. The non-transparent determination violates the applicable laws and general principles of good governance so that it has harmed the rights and interests of some prospective members of the Central Indonesian Broadcasting Commission who have spent their energy, thoughts and time, as well as costs to participate in the selection